Can fecal calprotectin be used as a biomarker of non-alcoholic fatty liver disease in obese adolescents? - Büşra Tetik Dinçer; Ayşe Merve Usta; Alev Kural; Nazlı Helvacı; Ahmet Uçar; Nafiye Urgancı (BMC Pediatrics)
Abstract Background The incidence of non-alcoholic fatty liver disease (NAFLD) is increasing with obesity, and it is believed that the ongoing low-grade inflammation in obesity and alterations in the enterohepatic axis contributing this process. This study aimed to determine the role of fecal calprotectin (FC) as inflammatory biomarker in obesity and NAFLD. Methods Between November 2022-August 2023, 31 obese and 10 healthy adolescents aged between 10 and 18 years enrolled in this prospective controlled study. Body mass index higher than 2 standard deviation is considered as obesity. Obese adolescents were divided into two subgroups: obese adolescents (n = 11) and Obese + NAFLD group (n = 20). NAFLD diagnosis was made with biochemical analysis or ultrasonography. FC levels and laboratory parameters analyzed in study group, while only FC samples taken from control group. Anthropometric and laboratory parameters were compared between groups. This study was registered in ClinicalTrials.gov (NCT06229184). Results The median (IQR P25-75) FC levels in the obese + NAFLD, obese and the healthy controls were 136.23 (43.36-332.04), 61.77 (29.70-285.92) and 38.95 (27.59–50.52) µg/g feces, respectively (p = 0.018). Subgroup analyses revealed that the significant difference was between the obese + NAFLD group and the control group (p = 0.02), while no significant differences were observed between the control and obese groups, or between the obese and obese + NAFLD groups. FC positivity rates were 20% (n = 2) in the control group, 54.5% (n = 6) in the obese group, and 75% (n = 15) in the Obese + NAFLD group (p = 0.018). Conclusions FC is significantly higher in obese adolescents compared to healthy peers, but no significant difference was observed between obese and obese + NAFLD groups. Further studies needed on this subject. Trial registration This trial is registered in ClinicalTrials.gov (Trial registration number [ClinicalTrials.gov ID] NCT06229184).